2018
DOI: 10.1002/anie.201811177
|View full text |Cite
|
Sign up to set email alerts
|

Design and Catalytic Asymmetric Construction of Axially Chiral 3,3′‐Bisindole Skeletons

Abstract: The first catalytic asymmetric construction of 3,3′‐bisindole skeletons bearing both axial and central chirality has been established by organocatalytic asymmetric addition reactions of 2‐substituted 3,3′‐bisindoles with 3‐indolylmethanols (up to 98 % yield, all >95:5 d.r., >99 % ee). This reaction also represents the first highly enantioselective construction of axially chiral 3,3′‐bisindole skeletons, and utilizes the strategy of introducing a bulky group to the ortho‐position of prochiral 3,3′‐bisindo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(69 citation statements)
references
References 121 publications
0
62
0
3
Order By: Relevance
“…Later, Kamikawa, Takahashi and Ogasawara reported an enantioselective desymmetrising ring-closing metathesis strategy to prepare axially chiral indole N -aryl compounds 19. Very recently, Shi and Tan independently reported a well-designed chiral phosphoric acid-catalyzed asymmetric synthesis of indol C(3)-aryl axial chirality;20 Gu reported Pd-catalyzed dynamic kinetic intramolecular C–H cyclization to construct indol C(3)-aryl atropisomers 21. However, no studies have been reported on the synthesis of indol C(2)-aryl axial chirality.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Kamikawa, Takahashi and Ogasawara reported an enantioselective desymmetrising ring-closing metathesis strategy to prepare axially chiral indole N -aryl compounds 19. Very recently, Shi and Tan independently reported a well-designed chiral phosphoric acid-catalyzed asymmetric synthesis of indol C(3)-aryl axial chirality;20 Gu reported Pd-catalyzed dynamic kinetic intramolecular C–H cyclization to construct indol C(3)-aryl atropisomers 21. However, no studies have been reported on the synthesis of indol C(2)-aryl axial chirality.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of a sterically demanding tertiary alcohol within 47 is essential for the regioselectivity of addition, with the analogous secondary benzylic alcohol undergoing selective reaction at the carbinol centre to form a racemic product. This work has subsequently been extended to the synthesis of highly substituted 3,3′‐bisindole products such as 51 from 3‐hydroxy‐3‐indolyloxindoles 50 (Scheme 25 b), [58] with excellent control of both axial and point chirality for a range of examples.…”
Section: Dehydrative C−c Bond Formationmentioning
confidence: 99%
“…Following a similar procedure, more complex and structurally rigid derivatives embedding four indole structures can be obtained by a three‐component reaction involving 2‐indolylmethanol 84 , indole and bisindoles 85 (Scheme ) . The 3,3′‐bisindolyl derivative primarily formed reacts with the alkylideneindolenine intermediate generated upon dehydration of 85 ( cf .…”
Section: Aromatic and Heteroaromatic Compoundsmentioning
confidence: 99%